مقومات التنافس المعاصرة للمؤسسة الاقتصادية من أجل التميز - خرخاش, سامية (Université de M'sila, 2009)
Because of the contemporary changeability, the economic institutions will either continue to exist or disappear completely. So, if they want to remain powerful and distinguished, they have to reach the highest degree of excellence by focusing on competitiveness to become the market leader. For that reason, the aim of this paper is to present intellectual and theoretical framework that deals with the meaning of rivalry and its real existence. Beside the attempt of this competitiveness to reexceed the role that should be played to create distinguished institutions especially in developing countries.